Changes in antioxidant enzyme activities in Eichhornia crassipes (Pontederiaceae) and Pistia stratiotes (Araceae) under heavy metal stress - Odjegba, V.J. (2007)
Whole plants of Eichhornia crassipes and Pistia stratiotes were exposed to various concentrations (0, 0.1, 0.3, 0.5, 1.0, 3.0 and 5.0 mM) of 8 heavy metals (Ag, Cd, Cr, Cu, Hg, Ni, Pb and Zn) hydroponically for 21 days. Spectrometric assays for the total activity of catalase, peroxidase, and superoxide dismutase in the leaves were studied. At the end of the experimental period, data referred to metal treated plants were compared to data of untreated ones (control). Heavy metals increased the activity of catalase, peroxidase and superoxide dismutase in both species and there was differential inducement among metals. Overall, Zn had the least inducement of antioxidant enzymes in both species while Hg had the highest inducement. The increase in antioxidant enzymes in relation to the control plants was more in E. crassipes than P. stratiotes. The results showed that E. crassipes tolerated higher metal concentrations in a greater number of metals than P. stratiotes.